Studi Komparasi Pengukuran Kinerja Finansial Pemerintah Daerah Kabupaten Kediri dan Blitar - Irafahmi, Diana Tien (Jurnal Ekonomi Modernisasi, 2009)
The purpose of this study is to measure and compare the financial performance of two governmental institutions located in East Java, Kediri and Blitar. Using data of budget realisation from that governmental institution over two periods—2007 and 2008—this study shows that Kediri had a better financial performance compare to Blitar. This study provides evidence to support the view that we are likely to see diversity in the result of financial performance measurement